ANALISIS AKSESIBILITAS WILAYAH HINTERLAND TERHADAP PUSAT KAWASAN BISNIS DI IBUKOTA KABUPATEN BOMBANA - Muslimin Makkaraeng Sikki; La Ode Muh. Magribi; M. Natsir (Universitas Halu Oleo, 2018)
Central Business District (CBD) plays very important roles in an area since this is where a regionbegins its growth and development before it moves outwards to the surrounding areas (hinterland). Thedevelopment of hinterland around the CBD of Rumbia needs to be analyzed to see the position andaccessibility of the hinterland in relation to the city centre. This study was set out to describe spreadingactivities in the hinterland areas that were affected by activities in the city centre of Rumbia.The purpose of this study was to analyze the accessibility of hinterland areas in its relative positionto the CBD of Rumbia city, to analyze the potensials for developing hinterland areas around the CBD ofRumbia in terms of their accessibility and land utilization, and to analyze population growth in thehinterland around the CBD of Rumbia in terms of the aspect of regional potensials for development.The study was conducted using a descriptive quantitative approach. Formula used was Hansen’saccessibility index, and variables under investigation were the number of population, the distance betweenareas, the extent of areas for residence, and employment opportunities in each area.Result of analysis showed that, based on Hansen’s accessibility index, the highest accessibilityindex was gained by the sub district of Rumbia (179.65 inhabitants per km2), followed consecutively by thesub district of North Rarowatu (126.31 inhabitants per km2), the sub district of Central Rumbia (72.68inhabitants per km2), the sub district of Rarowatu (30.82 inhabitants per km2), the sub district of Mata Oleo(28.33 inhabitants per km2), the sub district of Masaloka Raya (24.61 inhabitants per km2) and the subdistrict of Southeast Poleang (5.48 inhabitants per km2). The sub district of North Rarowatu has the biggestpotentials for development in comparison to the other six sub district, and it also has the biggest growth ofpopulation.Keywords : CBD, hinterland, accessibility, Hansen.